Sami Sieidis in a Nordic Context? - Mundal, Else (Journal of Northern Studies, 2018)
In the present article, the author discusses two Old Norse texts that may indicate that the Sami cult of sieidis had spread to the neighbouring Old Norse culture in the period before the Christianization of Norway. One of these texts is found in the Older Eiðsifaþing law, the law of the inland part of Eastern Norway. According to this law, it was prohibited to believe in (the power of) the finnar (Sami), and among their powerful objects, rót (the root of a tree) is mentioned. This root is in all likelihood a Sami sieidi that was sought out by Norwegians for help, probably for medical reasons. The other text is a notice in the Icelandic Landnámabók in which it is mentioned that a settler from Northern Norway worshipped some stones in the outfields on the border of his settlement, called Gunnsteinar. There are closer parallels to this outfields cult in Sami culture than in Old Norse culture.